Length of Stay in the Emergency Department and Its Associated Factors at Jimma Medical Center, Southwest Ethiopia - Ahmed, Abdulwahid Awol (Open Access Emerg Med, 2020)
BACKGROUND: Prolonged emergency department stays can adversely affect patient outcomes leading to an increased length of hospital admission and higher mortality. Despite this fact, there are few data describing emergency department length of stay and associated factors in Ethiopia. OBJECTIVE: To assess length of stay in the emergency department and its associated factors among patients visited adult emergency department of Jimma Medical Center, Jimma town, southwest of Ethiopia. METHODS: Institution-based cross-sectional study was conducted from April 9, 2018 to May 11, 2018. Overall, 422 patients presented during study period were sequentially included in the study. A semi-structured questionnaire was used to collect data through interview, observation and medical record review. The collected data were cleaned, entered to Epi-data 3.1 and exported to SPSS version 21 for binary and multivariable logistic regression analysis. To identify factors associated with outcome variable, candidate variables were fitted to multivariable analysis, and those with P-values <0.05 were considered as significantly associated. RESULTS: More than one-third, 162 (38.4%), experienced prolonged length of stay in the emergency department. The odds of prolonged stay were higher among rural area residency (AOR, 3.0; CI, 1.279–7.042), evening presentation (AOR, 4.25; CI, 1.742–10.417), and night-time presentation (AOR, 14.93; CI, 4.22–52.63), and having at least one diagnostic investigation (AOR, 4.48; CI, 1.69–11.88). However, participants who did not experience shift changes of nurses during their stay (AOR, 0.003; CI, 0.001–0.010) had a less prolonged stay. CONCLUSION: A significant proportion of patients experienced a prolonged stay at the emergency department. Age, rural residency, evening and night-time presentation, shift change and having a diagnostic investigation were predictors of prolonged stay. Thus, establishing time-targeted service for patients can reduce the length of stay.